EFFICACY AND SAFETY OF COMBINATION TREATMENT WITH ABATACEPT AND METHOTREXATE AND MONOTHERAPY WITH METHOTREXATE IN PATIENTS WITH POLYARTICULAR JUVENILE IDIOPATHIC ARTHRITIS - V. A. Kel'tsev; L. I. Grebenkina; N. S. Pryanichkova; S. А. Gorunov; N. V. Lagoda ("Paediatrician" Publishers LLC, 2012)
The results of efficacy and safety study of abatacept and methotrexate combination therapy (n=12) in comparison with methotrexate monotherapy (n =41) in patients with polyarticular juvenile idiopathic arthritis at the age of 4-17 years old are shown in this article. The duration of the observation was 1 year. Abatacept was introduced at a dose of 10 mg/kg at 1st, 2d and then - every 4th week. In 48 weeks clinical remission and decrease of laboratory markers of activity was registered in 35% of patients treated with abatacept and methotrexate and in 16% of patients treated only with methotrexate.